MORTALITY OF HIV/AIDS-INFECTED PEOPLE WITH ANTIRETROVIRAL THERAPY: A GENDER ANALYSIS - Putu Dian Prima Kusuma Dewi; Putu Sukma Megaputri; Lina Anggaraeni Dwijayanti; Dewa Ayu Putu Indra Pranita; Made Juniari Dewi (Belitung Raya Foundation, Indonesia, 2018)
Background: Mortality in people living with HIV/AIDS is one of measures to the success of its treatment. Study related to their deaths seen from gender is still very limited. Objective: The aim of this study was to determine the incidence rate of mortality between men and women living with HIV/AIDS and receiving antiretroviral therapy. Methods: This was a retrospective study using secondary data of HIV/AIDS-infected patients in Buleleng District Hospital in the period of 2006-2015. This research used survival analysis, Kaplan-meier, incident rate comparison and logistic regression with STATA SE 12. Results: A total of 1204 HIV/AIDS-infected patients’ data was included. The incidence of total mortality rates was 27.7 per 1000 person-years. Based on gender, the mortality in men (35 per 1000 person-years) was higher than women (14 per 1000 person-years) with the incidence rate ratio (IRR) of 2.39 (p 0.01). Fifty percent of cases of mortality occurred at 0.15 years of observation. The median time of mortality in men was 0.14 years (1.7 months) and in women was 0.15 years (1.8 months). The poor clinical condition was seen from a body weight <50 kg, which increased the risk of death with aOR 3.85 (p 0.01 CI 2.40-6.16). Nevirapine increased the risk of mortality (aOR 2.18; p 0.01; CI 1.18-4.03). and CD4 cell counts of ≤ 200 cells / mm3 reduced the risk of death by 69% (AOR 0.31; p 0.01; CI 0.18-0.53). Conclusion: The incidence of mortality in men was greater than it in women, which is caused by poor clinical conditions. It is better to evaluate the success of antiretroviral therapy by considering the needs of patients according to their gender. Further research is needed in regard to adherence of treatment and loss to follow-up events.